Fox be nimble - Marshall, James, 1942-1992. (New York : Scholastic, Inc., 1990)
Fox babysits for the miserable Ling children, makes a big scene when he slips on a skate and hurts himself, and gets to lead the band in the big parade
210
Keywords: Foxes -- Juvenile fiction; Foxes -- Fiction